Evaluation of light-curing units in rural and urban areas - Maan M. AlShaafi (Saudi Dental Journal)
Objectives: To evaluate the distribution of light-curing units (LCU) used in an urban area (Riyadh) and a rural area (Kharj) of Saudi Arabia, and to compare their irradiance values. Methods: The study involved three dental centers in urban areas and two in rural areas, all of which were parts of a single healthcare institution providing dental services. The light outputs (power mW) from 140 LCUs were measured by laboratory-grade spectrometry, and the irradiance (mW/cm2) was calculated from the tip area of each LCU. The minimum acceptable irradiance outputs for the quartz-tungsten-halogen (QTH) and light-emitting diode (LED) units were set at 300 and 600 mW/cm2, respectively. The ages of these units and the protocol used to light-cure the resins were also determined. Results: The total number of LCUs was 140, 112 (78%) in urban areas, and 28 (22%) in rural areas. In rural areas, only 7 of the 22 (32%) QTH units delivered irradiances greater than 300 mW/cm2 and were therefore considered clinically acceptable, whereas 4 of the 6 (66.7%) LED units delivered values greater than 600 mW/cm2. In urban centers, 43 of 61 (70.5%) LED units and 25 of 61 (49%) QTH units were considered clinically acceptable. Irradiance values for both QTH (P < 0.01) and LED (P < 0.05) units were significantly better in urban than in rural areas. Conclusions: Urban areas had a greater distribution of LCUs than rural areas. Overall, irradiance values were significantly higher in urban areas. Keywords: Resin restoration, Composite resin, Light-curing unit, QTH, LED